The Use of Prototype Theory in The Kurdish Languages - Abdullah, Abdullsalam N.; Saleh, Salwa F. (Humanities Journal of University of Zakho, 2017)
Prototype theory is a theory in categorical aspect and is used as a tool for explanation of how language categories are formed. In cognitive semantics categorization of language tools is counted as basic prototyping, that is why prototype, are tools for categorization. This research according to the basics of prototype theory and in general frame of cognitive semantics searches the (fruit) prototype in Duhok's students. The goal of this research is to determine the effect of different ages, geographic regions, economic conditions and... Etc. on the selected prototype. The type of this research is in fields, its way of performance is fielding and the data collection is by questionnaires. The samples are collected from fourth stage students, Kurdish language department of university of Zakho, high school students in Balqos village and Shinwar School in Duhok. The research hypotheses are about the effect of different ages, geographic regions, economic conditions and... etc. on the selected prototype.